(untitled) - Terpstra, John H. (New Jersey, 2004)
This book comprehensively documents step-by-step proven, working examples of Samba deployments. It is the perfect follow up book to the Official SAMBA-3 HOWTO and Reference Guide (0131453556). If you want to deploy Samba-3 with least effort, or if you want to become an expert at deploying Samba-3 without having to search for every piece of detail from the HOWTO, this book is the ticket to your destination. Each chapter begins with the description of a case problem and sets out specifications for the design of a solution. The second part of the chapter provides a detailed discussion of a fully documented step-by-step implementation. All example case configuration files, scripts and other tools are provided on a CDROM. This book is descriptive, provides detailed diagrams, and makes deployment of Samba-3 a breeze. Samba has an installed base of 12m, 30% of which are expected to update to Samba 3. Microsoft Windows Server has an installed base of about 16m, between 10-15% of which are expected to migrate to a non-Microsoft solution like Samba.
Keywords: Sampa (computer file),Unix (computer file),Microsoft windows (computer file)